Efeitos de sugestões e ordens sobre o seguimento de regras discrepantes em adultos com histórico experimental de seguimento persistente de regras - Gonçalves, Maíra (2025)
The rule-following behavior has been widely investigated due to its relevance. Despite presenting numerous advantages, rule-based learning can also lead to persistent rule-following. The present study aimed to investigate the effects of suggestions and commands on rule-following in adults with an experimental history of persistent rule-following. Twenty-nine university students participated and were exposed to a Matching-to-Sample procedure, in which they were required to select one of two comparison stimuli presented alongside a sample stimulus. In Phase 1, an initial evaluation of rule-following patterns was conducted. In the first and third blocks (C1 and C2 blocks), the contingencies were consistent with the rules, while in the second and fourth blocks (D1 and D2 blocks), the contingencies were altered without any signaling. Participants who exhibited a pattern of persistent rule-following in Phase 1 were exposed to Phase 2, which manipulated two types of rules (commands and suggestions). Participants were divided into three groups that differed regarding the type of rule presented in the corresponding blocks (C1, C2, and C3 blocks), namely, the Suggestion Group, the Command Group, and the Control Group. The discrepant blocks (D1 and D2) were identical for all groups. A mixed design was used (a single-subject ABAB reversal design and a group design). The results indicated that most participants who exhibited persistent rule-following inconsistent with contingencies in Phase 1 continued to follow the rule in Phase 2, regardless of the type of rule they were exposed to. Thus, manipulations of the formal properties of the rules did not have a differential effect on maintaining or abandoning discrepant rules. The findings also indicate that Phase 1 was effective in selecting participants with a pattern of persistent rule-following.